THE EFFECT OF MATERNAL GESTATIONAL DIABETES ON EARLY CHILDHOOD OBESITY AND METABOLIC PROFILE: A RETROSPECTIVE STUDY. - Kumar, Vijayant; Kumari, Anupam; Kumar, Anil; J P Narayan; Nisha, Swet; Prasad, Seema (Student's Journal of Health Research Africa, 2024)
Introduction Objective: To assess whether children born to mothers with GDM are at increased risk for early childhood obesity and altered metabolic markers compared to those born to non-diabetic mothers. Methods A retrospective cohort study was performed at Darbhanga Medical College and Hospital and Government Medical College, Bettiah, spanning from September 2015 to August 2016. A total of 100 mother-child pairs were included, consisting of 50 children born to mothers diagnosed with gestational diabetes mellitus (GDM) and 50 born to non-diabetic moms. Data were obtained from hospital delivery records, pediatric growth charts, and laboratory data. Anthropometric parameters (weight, height, BMI-for-age percentiles) and metabolic indicators (fasting glucose, serum insulin, lipid profile) were assessed between the two groups at ages 2 to 5 years. Results Children born to mothers with gestational diabetes mellitus exhibited a markedly elevated prevalence of overweight/obesity (38%) in contrast to controls (14%) (p < 0.01). The mean BMI percentiles and waist circumference were increased in the GDM group. A larger percentage of children in the GDM group exhibited insulin resistance (HOMA-IR >2.5), increased fasting glucose levels, and heightened triglycerides. No notable disparities in HDL or LDL levels were detected among the groups. Conclusion Prenatal exposure to maternal hyperglycemia is linked to a markedly elevated risk of early-onset obesity and metabolic disorders in offspring. These findings highlight the necessity for early screening, postnatal monitoring, and lifestyle modifications in children of mothers with gestational diabetes mellitus to mitigate the risk of future metabolic problems.